2007
DOI: 10.1002/ijc.22402
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of inflammation‐associated dihydrodiol dehydrogenases (AKR1C1 and AKR1C2) overexpression and drug resistance in nonsmall cell lung cancer cells by wogonin and chrysin

Abstract: Dihydrodiol dehydrogenase (DDH) is a member of the aldo-keto reductases superfamily (AKR1C1-AKR1C4), which plays central roles in the metabolism of steroid hormone, prostaglandin and xenobiotics. We have previously detected overexpression of DDH as an indicator of poor prognosis and chemoresistance in human non-small lung cancer (NSCLC). We also found DDH expression to be closely related to chronic inflammatory conditions. The aim of this study was to investigate the links between inflammation, DDH expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 50 publications
6
88
0
Order By: Relevance
“…Eletrophoresis was carried out in two 10% polyacrylamide gels with 4.5% stacking. One gel was processed for immunoblotting (20)(21)(22)(23)(24)(25)(26), and the other gel was stained with Coomassie blue. After electrophoresis, proteins on the first gel were transferred to a nitrocellulose membrane for immunoblotting.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eletrophoresis was carried out in two 10% polyacrylamide gels with 4.5% stacking. One gel was processed for immunoblotting (20)(21)(22)(23)(24)(25)(26), and the other gel was stained with Coomassie blue. After electrophoresis, proteins on the first gel were transferred to a nitrocellulose membrane for immunoblotting.…”
Section: Methodsmentioning
confidence: 99%
“…Using differential display alone or in combination with microarray, we previously identified a spectrum of NSCLCspecific tumor markers, such as dihydrodiol dehydrogenase (DDH), c-MET, matrix metalloproteinase (MMP) and short oncostatin M receptor (OSMRs), which were closely associated with resistance to chemotherapy, tumor recurrence, metastasis and poor prognosis (20)(21)(22)(23)(24). Although we expected that DDH would correlate with drug resistance (20)(21)(22) and MMP with tumor metastasis (23), DDH was not directly involved in cisplatin deactivation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flavonoid has been purified, with a defined chemical structure (Fig. 1), and in addition to the various pharmacological effects that it exerts, baicalein has been widely used to treat various inflammatory diseases, allergies, thrombosis and ischemia, as well as being a scavenger of oxygen free radicals (3)(4)(5)(6)(7)(8)(9)(10). Previously, it has been shown that bacailein not only has a therapeutic effect on non-tumorous diseases, such as acute liver failure and acute myocardial ischemia (11,12), but it also exerts an inhibitory effect on tumor diseases, including colorectal, prostate, liver, lung, skin, stomach and ovarian cancer (13)(14)(15)(16)(17).…”
Section: Chemical Structure and Physiological Function Of Baicaleinmentioning
confidence: 99%